Pembuatan Tiang Bendera Di SDN 13 Desa Bukit Rata, Kecamatan Kute Panang, Kabupaten Aceh Tengah - Nanda Arfan Fitra; Ilhamdi Almi; Isra Wesi; Yuliana Fitri; Jasniwan Jasniwan; Mahmud Basuki (Sejahtera: Jurnal Inspirasi Mengabdi Untuk Negeri, 2023)
Law No. 24 of 2009 Concerning Flags, Languages, State Symbols and National Anthems, it has been generally defined that a flag is a strong symbol to identify and represent an identity of a nation or group. Flags are used in agencies, offices, schools, and so on. Seeing the importance of the flag as one of the symbols of the country and many agencies that already have flagpole facilities, one of which is an institution in the field of education. Based on the results of field observations made, there are major problems related to flags, where in one of the elementary schools in Bukit Rata Village, which is a part of Kute Panang District, Central Aceh District, there are still many or minimal facilities at the school, one of which is no pole facilities. flag. Based on the results of discussions with the principal and teachers, the authors took the initiative to make flagpoles. The method used is to go directly to the field or practice directly to the field to build and erect the flagpole. The purpose of this flagpole installation activity is expected to increase a sense of nationalism, love for the motherland, and become one of the flag ceremony facilities at SDN 13 Kute Panang school located in Bukit Rata Village. The activity of installing flagpoles at SDN 13 Kute Panang is a form of community and state service carried out by the author.